Promoting Traditional Chinese Winter Sport Participation: Cultural Capital and Demands of Bingxi - Wang, Xinghua (Technium Social Sciences Journal, 2022)
As the 2022 Beijing Winter Olympic Games approach, promoting the winter sport participation in China is essential and important. However, most of winter sports participants are one-time player, and it could be due to the lack of winter sports culture in the Chinese public. So, developing and promoting the traditional Chinese winter sports may help managers to build a endogenous winter sport culture. Bingxi is a series of ice sport event in ancient China, which is the one of the most representative traditional Chinese sports, which is unique in Chinese history. The present study applied a historical method to explore the three forms of cultural capital in Bingxi. And developed a Demands Scale for Cultural Capital in Bingxi (DSCCB) to measure the participation demands in Bingxi of different group people. Residents (n=621) of Shenyang (capital city in Qing Dynasty) participated in this study. Discussions are centered on the target group of the three forms of cultural capital in Bingxi, and offer a proposal for promoting Bingxi in the future.